Do Muslim CEOs and Muslim stakeholders prefer Islamic debt financing? - Brahmana, Rayenda Khresna; You, Hui Wei (Elsevier Inc., 2021)
This study examines the relationship between religiosity and Islamic debt financing based on Malaysian non-financial listed firms from 2012 to 2018. We find that Muslim CEOs allocate more Islamic financing in their debt financing compared to non-Muslim CEOs, which support the upper echelons theory. However, we find that the sociological pressure from Muslim Stakeholders display no significant effect on Islamic financing. Interestingly, we further find that Islamic debt financing will incline no matter whether the Muslim population is high or low if the CEO was a Muslim. This implies that our findings support the upper echelon theory, but not the stakeholder orientation theory